Depletion of γ-glutamyl cyclotransferase suppresses the proliferation, migration and invasion of breast cancer cells accompanied by the activation of PI3K/AKT/mTOR pathway - De He; Weiheng Cui; Xijiao Pang; Jiale Dong; Quanwei Qiu; Hongmei Dong; Ruijun Zhao (Scientific Reports)
Abstract Breast cancer is a prevalent and deadly disease affecting women worldwide. Recent studies have shown that γ-glutamyl cyclotransferase (GGCT), an enzyme involved in glutathione metabolism, is consistently upregulated in various cancers. However, its specific role in breast cancer remains poorly understood. This study aimed to investigate the functional role of GGCT in breast cancer. Bioinformatics, immunohistochemistry and immunoblotting analysis revealed that GGCT is significantly upregulated in breast cancer tissues, and its high expression is associated with poor survival outcomes. The knockdown of GGCT significantly suppressed MCF-7 and SKBR-3 cell activities. Cell proliferation decreased by 29.4–45.9%, and colony formation reduced by 51.5–56.6%. Migratory ability diminished by 36.8–49.1%, while invasion capability declined by 35.2–55.0%. Moreover, GGCT silencing reduced epithelial-mesenchymal transition (EMT) and inhibited the PI3K/AKT/mTOR signaling pathway. Notably, E-cadherin expression significantly increased in MCF-7 and SKBR-3-shGGCT cells, with changes ranging from 2.1-fold to 5.4-fold. Conversely, N-cadherin expression decreased by 54.2–84.2% in both cell lines. Vimentin expression also decreased significantly, with reductions of 58.8–83.0%. Further analyses indicated that p-AKT expression in MCF-7 and SKBR-3-shGGCT cells decreased by 51.4–84.8%. Additionally, p-mTOR expression was reduced by 71.2–87.2% in both cell lines, compared to shCtrl. Our data highlights the crucial role of GGCT in regulating EMT and the progression of breast cancer. The findings suggest that GGCT not only serves as a valuable prognostic marker but also represents a potential target for therapeutic interventions in breast cancer patients.